The Clinical Risks of Infection Associated with Endoscopy - Alistair E Cowen (Canadian Journal of Gastroenterology)
The cleaning of flexible endoscopes is difficult and time consuming. Any method of attempted sterilization or high level disinfection will fail if prior cleaning has been defective. Inadequate reprocessing of endoscopes may result in patient to patient transmission of serious bacterial and viral diseases or infection with endemic hospital pathogens. Antibiotic prophylaxis is required to prevent septicemia and bacterial endocarditis in high risk patients undergoing specific endoscopic procedures. Prevention of serious endoscopy-associated clinical infections requires strict compliance with detailed reprocessing protocols by specially trained nursing staff.